Rupture of the urethra caused by a calculus - Eckstein, Herbert B.; Marulyalı, Keriman; Tatman, Neclâ (The Turkish Journal of Pediatrics, 1959)
A case of extravasation of urine following perforation of the urethra by a calculus is described. The patient died of a B. coli septicaemia.